Análisis jurídico de la aplicabilidad de la tutela efectiva, imparcial y expedita estatal al medio ambiente como bien jurídico protegido. - Martínez Robalino Dayana Karina (2025)
In this research project, my primary objective is to conduct a legal analysis on the applicability of effective, impartial, and expeditious state protection to the environment as a legally protected interest. This is particularly relevant given that since 2008, Ecuadorian legislation recognizes nature as a subject of rights; they are recognized as such, granting ordinary citizens, social organizations, public and private entities the authority to resort to judicial and constitutional bodies to litigate the respect for their rights in circumstances where nature is affected. Currently, for example, it is necessary to preserve the environment due to the excessive use of plastics as well as industrial waste, disregard for water usage, excessive use of chemicals, and other factors that gradually degrade the environment we live in, which is essentially nature. Addressing this need, the Ecuadorian legislation in the Constitution of the Republic of Ecuador specifies the right to protection as one of the most important, aiming to safeguard the rights that Ecuadorian citizens are entitled to. This constitutional mandate recognizes nature as a subject of rights deserving of this protection and the application of effective, impartial, and expeditious legal guardianship. This protection extends not only from judicial and constitutional bodies but also from public entities where the state plays a crucial role as a net protector of nature, considering it a fundamental element for life, primarily for humans and the species that inhabit the planet. Through a detailed legal approach, relevant legal and regulatory provisions supporting environmental protection will be reviewed. Landmark cases and jurisprudence related to the effective protection of the environment will be explored, assessing the effectiveness of existing legal mechanisms. The analysis will focus on identifying possible gaps, challenges, and opportunities in the application of effective protection to the 6 environment, considering the complexity of contemporary environmental issues. Based on these findings, legal recommendations and reflections will be proposed to strengthen and enhance state protection of the environment, ensuring the preservation of this fundamental legal interest for present and future generations. It's a robust strategy. By combining the review of information from books, the web, and scientific articles with an analysis of current legal regulations, you will gain a comprehensive perspective. This approach will allow to ground its research in doctrine and law. By elucidating the effectiveness of nature protection rights and the role of the State as the primary enforcer, it will contribute to a thorough and well-founded analysis in this research work. The research methodology is qualitative, utilizing the dogmatic and interpretative methods of constitutional and legal norms. Through these methods, a response to the addressed problem is provided based on the best possible reconstruction allowed by the legal material available. Additionally, since the social phenomena studied in this work are measurable and quantifiable, I will measure and establish causal relationships between variables to explain the research problem and current social reality. Keywords: Effective Protection, Protection Rights, Subject of Rights, Rights of Nature, Active Standing, Environment